Personal Thinking on the Creative Directions of Chinese Contemporary Zheng Music - Liu, Peng (Revista Vórtex, 2020)
In this article, composer Peng Liu investigates the role of the Zheng instrument in Chinese new music scene. The composer focuses on three main approaches on how Zheng music has been written so far: the preservation of tradition, the modern development, and the extreme use. Peng also talks about the resistance from traditional Zheng players when performing pieces from the new music repertoire, and the encouragement to experimentation led mainly by Chinese composers. Although the text is a personal response by the composer, Peng is motivated to contribute to the development of new music repertoire for Zheng [note by editor].